Attitude of school teachers towards inclusive education : a case study on private school teachers in the Klang Valley - Faizanah binti Abdul Alim Sidique (Kulliyyah of Education, International Islamic University Malaysia, 2019)
Inclusive Education is a concept that accommodates the placement or inclusion of special educational needs students in a regular education classroom. In Malaysia, despite the government initiatives to amend the education policy towards inclusive education, there is a gap left by the inadequacies in the implementation of inclusive education programs. This study aims to determine the teachers attitude towards students with special educational needs in private/international schools. The teachers from the REAL School, Suria Campus were chosen for this study. A questionnaire was administered as the research instrument containing short structured questions which were on a Likert scale. Data was analyzed using the Statistical Package for Social Sciences (SPSS) software package. The statistical procedures that was utilized was namely descriptive statistics, independent sample t-test, one-way ANOVA and simple linear regression analysis. The study found that majority teachers often find it difficult to handle students with specific learning difficulties in the mainstream classroom. Therefore, most of the teachers agreed that they need training in order to appropriately teach students with specific learning difficulties. In general, the results from this study shows that majority of the respondents have an infavourable attitude towards inclusion of students with specific learning difficulties in regular classroom. The results also reveal that Malaysia is still lack of teachers who are specialized in special education and special education training are not provided adequately to general education teachers. In conclusion, there are evidence which confirm that the new amendments in the education policy towards inclusive education in Malaysia is done without considering on educating and preparing teachers to handle students with learning disabilities in the general school. Several recommendations are proposed to be included in the review of the training curriculum for pre-service teachers. In addition, the school administrators and general education teachers are also recommended to be sent for in-service training in order to keep them abreast about the shift in the education system towards inclusive education.